(untitled) (Revista de Medicina Clinica, 2024)
Background: Patients with rheumatoid arthritis treated with methotrexate may have hematological damage, including myelosuppression, leukopenia, neutropenia, and megaloblastic anemia. The hematological toxicity causes up to 25% of patients to discontinue treatment due to risk of mortality. Pancytopenia is among the toxicities of methotrexate and is difficult to prevent, as it can appear unexpectedly during therapy. Case report: A 70-year-old female patient with a diagnosis of rheumatoid arthritis, attended due to symptoms such as asthenia, adynamia, fever and pain in the oral mucosa. The blood count reports hemoglobin of 7.5 g/dL, leukocytes of 1700 µl, and platelets of 13,000/mm3. The patient is diagnosed with myelosuppression secondary to high doses of methotrexate, she is managed with blood products, hydration, folinic acid, granulocyte colony-stimulating factor rHu-G-CSF, and recombinant glycoprotein. She reports stable. Conclusions: Although methotrexate is effective in the treatment of many diseases, including rheumatoid arthritis, whether intentional or mistaken, especially in older adults, can cause serious side effects, including hematologic toxicity and increased risk of infections. The management of myelosuppression secondary to methotrexate has three main objectives, elimination of methotrexate from the bloodstream, therapy with folinic acid, and treatment of pancytopenia.